Human Health and Recycled Wood Materials Containing Creosote Oil: Empirical Evidence from Research - Barbara KSIT; Tomasz BŁASZCZYNSKI (Communications of International Proceedings, 2021)
This article discusses –based on timber materials – the intricacies in terms of recycling structural elements protected with an impregnate containing a long-lasting carcinogenic chemical compound, which is still approved for use within the EU. It presents the emission standards for hazardous waste. It also touches upon environmental hazards caused by creosote oil used as an impregnate in timber structures. It shows the concentrations of PM10 and PM2.5 pollutants in the world and in Poland over selected periods. It also reviews the factors hindering a comprehensive approach to the recycling of such products and selected disposal methods. The structure of timber, which was non-impregnated and was in good condition and impregnated timber in disrepair state was compared. It has been shown that although the impregnation impregnation with creosote oils is to improve their resistance against wood decaying fungi and wood destroying insects, it cannot be used to protect wooden materials and the elements should not be recycled for commercial purpose but disposed of.
Keywords: Benz(A)Pyrene; Recycling; Timber; Creosote.